The Effect of Using Multi-Skilled Workforce on the Flexibility of Project Resource Scheduling and Project Costs - Manyi, Thulisile; Sibanda, Rosemary; Katrodia, Ankit (Journal of Economics and Behavioral Studies, 2018)
The introduction of multi-skilling within organisations is normally conducted with the aim of improving efficiency, quality, production and cost-effectiveness. The study addressed the effect of using multiskilled workforce in the execution of project activities by studying the changes in project execution resource scheduling flexibility and project costs in response to workforce multi-skilling strategy. A quantitative research design was used, to test the concept of workforce multi-skilling to predict its influence on project resource scheduling, project cost saving, project duration, effect on optimal utilization of project technicians and members if adopted at Eskom PTM Central Group department. An electronic questionnaire was distributed to collect data and statistical analysis of data was conducted. The hypothesis testing performed concluded as follows; H1: The use of multi-skilling provides for flexible project resource scheduling; the research hypothesis was accepted. H2: Multi-skilling has a positive effect on the project cost savings; the research hypothesis was rejected. H3: The use of multi-skilling has no significant impact on project duration; the research hypothesis was rejected. H4 (i): The findings show that a positive relationship between multi-skilling and job redesign exists, and H4 (ii): Multi-skilling therefore has a positive impact on the adoption of multi skills; both research hypotheses were accepted.